Left atrial volume provides independent and incremental information compared with exercise tolerance parameters in patients with heart failure and left ventricular systolic dysfunction - Rossi, Andrea (BMJ Group, 2007)
OBJECTIVE: Left atrial volume (LAV) is a powerful predictor of outcome in patients with chronic heart failure (CHF) independently of symptomatic status, age and left ventricular (LV) function. It is unknown whether LAV provides independent and incremental information compared with exercise tolerance parameters. METHODS: 273 patients with CHF (mean (SD) 62 (9) years; 13% female) prospectively underwent echocardiography and exercise testing with maximal oxygen consumption (Vo(2)). The primary end point was composite and included cardiac death, hospitalisation for worsening heart failure or cardiac transplantation. RESULTS: At Cox proportional hazard analysis, LAV normalised for body surface area (LAV/BSA) was strongly associated with mortality (hazard ratio (HR) = 1.027 (95% CI 1.018 to 1.04), p<0.001). The predictive value of LAV/BSA was independent of Vo(2) and LV ejection fraction (EF) (HR = 1.014 (1.002 to 1.025), p = 0.02; HR = 0.95 (0.91 to 0.99), p = 0.02; HR = 0.89 (0.82 to 0.98), p = 0.02 for LAV/BSA, EF and Vo(2), respectively). Receiver operator characteristic (ROC) curve analysis identified the best cut‐off values for prediction of the end point. LAV/BSA >63 ml, EF <30% and Vo(2) <16 ml/kg/min were considered to be risk factors. Patients with three risk factors had an HR of 38 (95% CI 11 to 129) compared with patients with no risk factors. CONCLUSION: LAV provides powerful prognostic information incrementally and independently of Vo(2). LAV, EF and Vo(2 )can be used to build a risk prediction model, which can be used clinically.